Highly lethal genotype I and II recombinant African swine fever viruses detected in pigs - Zhao, Dongming; Sun, Encheng; Huang, Lianyu; Ding, Leilei; Zhu, Yuanmao; Zhang, Jiwen; Shen, Dongdong; Zhang, Xianfeng; Zhang, Zhenjiang; Ren, Tao; Wang, Wan; Li, Fang; et al. (Nature communications, 2023)
African swine fever virus (ASFV) poses a great threat to the global pig industry and food security. Currently, 24 ASFV genotypes have been reported but it is unclear whether recombination of different genotype viruses occurs in nature. In this study, we detect three recombinants of genotype I and II ASFVs in pigs in China. These recombinants are genetically similar and classified as genotype I according to their B646L gene, yet 10 discrete fragments accounting for over 56% of their genomes are derived from genotype II virus. Animal studies with one of the recombinant viruses indicate high lethality and transmissibility in pigs, and deletion of the virulence-related genes MGF_505/360 and EP402R derived from virulent genotype II virus highly attenuates its virulence. The live attenuated vaccine derived from genotype II ASFV is not protective against challenge of the recombinant virus. These naturally occurring recombinants of genotype I and II ASFVs have the potential to pose a challenge to the global pig industry. Potential recombination of African swine fever virus genotypes is not well understood. Here, Zhao et al. report naturally occurring ASFVs carrying mosaic genomes of genotype I and II and show that the recombinant virus is lethal in pigs and evades the immunity induced by genotype II live vaccine.